Novel FZD4 and LRP5 mutations in a small cohort of patients with familial exudative vitreoretinopathy (FEVR). (4th March 2021) - Carrera, William; Ng, Caleb; Desler, Caroline; Jumper, J. Michael; Agarwal, Anita
ABSTRACT: Purpose : To report novel mutations in the FZD4 and LRP5 genes, associated with familial exudative vitreoretinopathy (FEVR), and to correlate with clinical features of 7 FEVR patients. Methods : In this retrospective case series, 7 patients who had undergone genetic panel testing and carried a diagnosis of FEVR were identified. Comprehensive ophthalmic examination and direct DNA sequencing of FEVR-associated genes were performed in all patients. Identified sequence variants were analyzed in silico . Results : Eight mutations were identified amongst the 7 patients, that included 4 FZD4 mutations and 4 LRP5 mutations. Four novel mutations were identified, two in FZD4 (c.615delC, p.Y206MfsX34) and (c.964A>T, p.I322F), and two in LRP5 (c.2585A>T, p.D862V) and (c.1412 + 1 G > A, splice donor). A broad phenotypic spectrum was noted and no clear genotypic-phenotypic correlation was observed. Conclusion : These findings expand the mutation spectrum of FZD4 and LRP5 .